2001
DOI: 10.1046/j.1365-2761.2001.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Portuguese strains of Yersinia ruckeri isolated from fish culture systems

Abstract: A total of 23 Portuguese strains of Yersinia ruckeri, the causative agent of enteric redmouth disease (ERM), were comparatively studied by means of lipopolysaccharide (LPS) and outer membrane protein (OMP) analysis, plasmid profiling and ribotyping in order to investigate the heterogeneity among isolates and the usefulness of these methods as epidemiological markers. Only two LPS profiles were observed among the isolates studied, corresponding with the serotypes O1 and O3 of Y. ruckeri. A higher heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…The different LPS patterns exhibited by the Chilean isolates corresponded to those of serotypes O1a, O1b and O2b. Differences in the number of bands and the interband distances among serotypes are consistent with results previously reported for Y. ruckeri by other authors (Romalde et al 1993, Sousa et al 2001. Results of OMP analysis of the Chilean Y. ruckeri isolates supported those from previous studies (Romalde et al 1993, Sousa et al 2001, in which observations of distinct protein profiles were observed related to the different serotypes of Y. ruckeri.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The different LPS patterns exhibited by the Chilean isolates corresponded to those of serotypes O1a, O1b and O2b. Differences in the number of bands and the interband distances among serotypes are consistent with results previously reported for Y. ruckeri by other authors (Romalde et al 1993, Sousa et al 2001. Results of OMP analysis of the Chilean Y. ruckeri isolates supported those from previous studies (Romalde et al 1993, Sousa et al 2001, in which observations of distinct protein profiles were observed related to the different serotypes of Y. ruckeri.…”
Section: Discussionsupporting
confidence: 91%
“…Differences in the number of bands and the interband distances among serotypes are consistent with results previously reported for Y. ruckeri by other authors (Romalde et al 1993, Sousa et al 2001. Results of OMP analysis of the Chilean Y. ruckeri isolates supported those from previous studies (Romalde et al 1993, Sousa et al 2001, in which observations of distinct protein profiles were observed related to the different serotypes of Y. ruckeri.In addition, genetic variability was observed in Chilean Yersinia ruckeri isolates using REP-and ERIC-PCR techniques, establishing, respectively, 2 and 3 groups related with the serotype. ERIC-PCR showed higher discriminatory power than REP-PCR, but both techniques could have some value as tools to study ERM epidemiology.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This approach allowed six distinct clonal groups to be distinguished among serotype O1 isolates and was able to differentiate between the classical Hagerman and the newly emerged biotype 2 strains (21). Subsequently, OMP analysis has played an important role in various epidemiological analyses of Y. ruckeri (9,15,24,(29)(30)(31).…”
mentioning
confidence: 99%
“…In the sampling carried out at day seven after the injection, Y. ruckeri was re-isolated from the visceral organs and blood of moribund fish using a tryptic soy agar (TSA) medium (Austin et al, 2003, Sousa et al, 2001. Hematological and non-specific immune parameters, oxidative stress indices (OSI) and histopathological examinations were analyzed in twenty-one fish from each experimental group (the total number of fish: 105).…”
Section: Experimental Infection With Yersinia Ruckerimentioning
confidence: 99%